Tumescent non-tumescent technique for split thickness skin graft harvesting - Rajendran, M. K. (International Surgery Journal, 2018)
Background: Split-thickness skin graft failures can be attributed to flaws in the recipient bed which has to be well prepared. Tissues with limited blood supply such as bone, tendons, cartilage or sites with necrotic tissue or infection do not accept skin grafts. Adrenaline is used to harvest skin grafts due to its vasoconstriction effect which limits blood loss. The aim of our study was to determine skin graft take after tumescent technique compared to a non-tumescent technique for harvesting. Methods: Two treatment groups of patients who fulfilled the inclusion criteria were randomly assigned. Forty patients underwent split-thickness skin graft harvesting with tumescent technique and forty patients underwent non-tumescent split-thickness skin graft harvesting. The recipient site was opened in both groups on the fifth day after surgery and take rate assessed. The donor site was assessed on day ten and if not healed, followed up for three weeks. Results: There was a statistically significant association between skin graft take rate and skin grafting technique (p=0.011). The mean graft take rate was 2.5% higher in the tumescent group compared to the non-tumescent group (96.3% compared to 94%). On day 10, there was no difference in percentage healing of donor sites between the tumescent and non-tumescent groups, p=0.562. Conclusions: Tumescent technique significantly reduced intraoperative blood loss. It is safe, inexpensive and easy to use. The subdermal adrenaline/saline injection creates a smooth, dense surface which assists debridement and donor harvesting.